How can word games help elementary school students to develop vocabulary - Fazilat Abdurahmonovna Musayeva (Academia One Publishing, 2023)
This article discusses the mistakes made by teachers in improving the vocabulary of elementary school students who do not have high language skills and how they affect students. In solving such problems, there is another more effective way to improve vocabulary, word games, attempts to discover their useful aspects.
Keywords: vocabulary; word games; memorize; definitions